2013
DOI: 10.1530/eje-12-0891
|View full text |Cite
|
Sign up to set email alerts
|

BMP system expression in GCs from polycystic ovary syndrome women and the in vitro effects of BMP4, BMP6, and BMP7 on GC steroidogenesis

Abstract: Background: The bone morphogenetic proteins (BMPs) are growth factors involved in the folliculogenesis. Alteration in their expression may compromise the reproductive process in disease such as the polycystic ovary syndrome (PCOS). This study investigated the expression and role of granulosa cell (GC) BMP from normal cycling and PCOS women. Methods and results: This prospective study was performed in GCs obtained from 14 patients undergoing IVF: i) six women with normal ovulatory cycles and tubal or male infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…In this sense, Fatehi et al (2005) found no BMP4 protein expression in granulosa cells of growing follicles, despite having shown mRNA expression in granulosa and theca of antral follicles less than 8 mm in diameter. However, Glister et al (2010) and Kayani et al (2009) showed BMP4 mRNA expression and immunoreactive protein in both theca and granulosa cells, although BMP4 transcripts were more abundant in theca than in granulosa cells, in agreement with earlier immunocytochemical evidence in cattle (Glister et al 2004) and other species (Khalaf et al 2013).…”
Section: Discussionsupporting
confidence: 64%
“…In this sense, Fatehi et al (2005) found no BMP4 protein expression in granulosa cells of growing follicles, despite having shown mRNA expression in granulosa and theca of antral follicles less than 8 mm in diameter. However, Glister et al (2010) and Kayani et al (2009) showed BMP4 mRNA expression and immunoreactive protein in both theca and granulosa cells, although BMP4 transcripts were more abundant in theca than in granulosa cells, in agreement with earlier immunocytochemical evidence in cattle (Glister et al 2004) and other species (Khalaf et al 2013).…”
Section: Discussionsupporting
confidence: 64%
“…The expression of BMP/GDF ligands and their receptors in human ovarian tissues is listed in Table III. In the human ovary, BMP2, BMP4, BMP5, BMP6, BMP7 and BMP8A are expressed in the GCs from normally cycling and polycystic ovary syndrome (PCOS) women (Khalaf et al ., 2013). In concert with this study, a study using isolated human pre-antral follicles that compared the expression levels of BMPs in five size-matched populations demonstrated that BMP6 and BMP15 are the most abundantly expressed ligands (Kristensen et al ., 2014).…”
Section: Intra-ovarian Bmps and Oocyte–somatic Cell Interactionsmentioning
confidence: 99%
“…(2002)Luteinized GCmRNA & ProteinRT-PCR, Western blotHuang et al . (2009)FF (0.83–53.9 ng/ml)ProteinELISAALK2Luteinized GCmRNART-qPCRKhalaf et al . (2013)ALK3Luteinized GCmRNA & ProteinRT-qPCR, IHCKhalaf et al .…”
Section: Intra-ovarian Bmps and Oocyte–somatic Cell Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In PCOS patients, Khalaf et al reported an over expression of BMP-6 and BMPR1A in granulosa cells. They showed that BMP-6 and BMP-7 exerted a stimulatory effect on basal E2 production while BMP-4 and BMP-6 inhibited FSH-induced E2 production [20]. It is now well recognized that BMPs play an important regulatory role in the mammalian ovary, central to follicular recruitment and selection mechanisms.…”
Section: Introductionmentioning
confidence: 99%